Penyelesaian Kredit Macet Pihak Debitur Dan Perlindungan Hukum Bagi Kreditor Di Bank Ntt Cabang Oebobo Kupang - Stefanus Don Rade; Vinsensius Tamelab; Godeliva MGMabilani; Giovani DB Nongbut (Universitas Sains dan Teknologi Komputer, 2023)
Credit is the provision of money or bills that can be equated with it, based on a loan agreement or agreement between a bank and another party that requires the borrower to pay off his debt after a certain period of time with interest. The problems that arise when there is bad credit or bad credit are the risks contained in every credit provided by the bank. The risk is that the debtor has difficulty fulfilling the obligation to return credit on time. The inability of debtors to pay their debts has a negative impact on creditors as credit distributors. This study aims to determine the causes that result in bad credit from debtors of Bank NTT Kupang Main Branch, and find out how the settlement process is. This study uses empirical juridical research with statutory, conceptual, and sociological approaches. The causes that affect bad credit are intentional elements, namely the debtor consciously does not want to pay his credit and intentional elements, namely the existence of force majeure. The creditor has the right to use the executorial title as stated in the fiduciary guarantee certificate, if the debtor defaults. Creditors also have the right to sell objects that are objects of fiduciary guarantees through public auctions and settlement of receivables from sales or private sales which are carried out based on a mutual agreement between the creditor and the debtor